Affordable, Compact and Infection-Free BiPAP Machine - Singh, Gaurav Pal (Trans Indian Natl. Acad. Eng., 2020)
Critical cases of COVID-19 require respiratory support provided primarily by mechanical ventilators. But, as per the current trend, about 15% of the cases require hospitalization and less than 5% cases are critical. Due to the massive number of COVID-19 cases all over the world, the ventilator requirement is increasing, and these traditional ventilators are quite expensive and are occupied for the critical cases, thus available in limited numbers. In this regard, BiPAP (Bilevel Positive Airway Pressure) ventilation support can be used for the less critical cases where patients do not require intubation by specialized staff and also minimizing the risk of infection during the procedure. The current article aims to deliver a design of an inexpensive BiPAP with an infection-free exhaust. BiPAP is a mode of ventilation which maintains positive pressure for air intake, and a low or zero pressure is created for expiration. The BiPAP suggested in the current article uses an air blower connected to an Arduino via a speed controller, the level of pressure and breathing rate are programmed in the Arduino, thus, the blower functions in BiPAP mode. The 3D printed mask proposed here comprises of a unique design for the intake and exhalation of air; and comprises of two sizes to fit all adults while avoiding any leakage. The design suggested is further tweaked for emergency use to support up to four patients using a single BiPAP. The mass production of the same would cost approx. INR 6500 or 85 USD.